1966
DOI: 10.1136/jcp.19.4.352
|View full text |Cite
|
Sign up to set email alerts
|

Plasma fibrinogen and plasminogen levels in health and in ischaemic heart disease

Abstract: SYNOPSIS Plasma fibrinogen and plasminogen levels were measured in 122 male and 56 female healthy adult subjects and in 64 men with ischaemic heart disease. Plasma fibrinogen levels were found to rise markedly and progressively with age in both male and female healthy subjects; plasminogen showed only a slight rise with age. No sex differences were found for either fibrinogen or plasminogen. The correlation between plasminogen and fibrinogen levels was low, reaching the 5 Y.level of significance only in men. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
1

Year Published

1968
1968
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(37 citation statements)
references
References 15 publications
6
30
1
Order By: Relevance
“…The previously described rise in the plasma fibrinogen concentration with age (Ogston and Ogston, 1966) This study has demonstrated a progressive and considerable increase in the level of FR-antigen with age. The significance of such a rise is uncertain.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The previously described rise in the plasma fibrinogen concentration with age (Ogston and Ogston, 1966) This study has demonstrated a progressive and considerable increase in the level of FR-antigen with age. The significance of such a rise is uncertain.…”
Section: Discussionsupporting
confidence: 76%
“…Ten male and 10 female healthy medical students, doctors, and technicians, aged (Ogston and Ogston, 1966) of the method described by Ratnoffand Menzie (1951).…”
Section: Subjects Studiedmentioning
confidence: 99%
“…Normal Fg levels in human serum average ϳ3 mg/ml (43,44), and Fg is detected in human sputum (2-20 g/ml) (45) and saliva (46) and is localized on human tonsils (47). Upon addition of Fg at a conservatively low level of 8 g/ml (1/750th of normal serum levels), we observed a further reduction in OKP7 cell adherence by the WT and complemented mutant GAS strains, but not the ⌬M1 mutant ( Fig.…”
Section: M1 Protein Reduces Pharyngeal Cell Adherence and Invasion Wmentioning
confidence: 99%
“…It is well known that patients suffering from coronary heart disease (CHD) or stroke show elevated fibrin ogen values [1,2] and the severity and the number of vessels involved are correlated with the extent of fibrinogen levels [3]. Fur thermore.…”
Section: Introductionmentioning
confidence: 99%